Study of Prenatal Arsenic Exposure and Reproductive Health Outcome in Bangladesh (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective : There is growing concern that exposure to arsenic during pregnancy can have adverse effects on the developing fetus. To investigate the effect of arsenic exposure on reproductive health outcomes this study was carried out.Materials and methods : This prospective birth cohort study was carried out by Harvard School of Public Health and Dhaka Community Medical College & Hospital in 2004 through the Sirajdikhan and Birahimpur community clinics as a pilot project. The study included 421 pregnancies at the time of enrollment. Water samples were collected at the time of enrollment and within one month of delivery from the tubewell of each participant identified as their primary source of drinking water. These samples were analyzed by inductively coupled plasma mass spectrometry.Results: Of 421 pregnancies, 38 women withdrew from the study or were lost to follow up (9.0%), 30 resulted in spontaneous abortion or miscarriage (7.1%), 32 were stillbirths (7.6%) and 321 were live births (76.2%). At the time of enrollment, the average drinking water arsenic exposure level was 31.6 ?g/L (standard deviation, 83.7 ?g/L; range,